Freehand sketching and its relationship with the creativity of architecture students, Piura – 2024 - Escobar Carreño, Abner Josue; Castellano Arellano, Pamela del Carmen; More Ayala, Samantha Aymee; La Rosa-Boggio, Diego Orlando (LACCEI, 2025)
The objective of the research was to determine the relationship between the use of freehand sketching and the creativity of architecture students in Piura, Peru. The research was non-experimental, quantitative, basic and correlational. The population consisted of 3,851 architecture students who belonged to the five universities in the city of Piura and the sample was 350 students. After the students answered two questionnaires, the results were that freehand sketching had a significant relationship (p = 0.000 < 0.050) at a very high level (Spearman’s Rho coefficient of 0.909) with the creativity of architecture students. That is, the more freehand sketching was used by students, the more creative they were when proposing the designs of their architectural projects.